Social Inclusion and Exclusion: A Review - Rawal, Nabin (Dhaulagiri Journal of Sociology and Anthropology, 2008)
The concept of social exclusion/inclusion figured prominently in the policy discourse in France in the mid 1970s. The concept was later adopted by the European Union in the late 1980s as a key concept in social policy and in many instances replaced the concept of poverty. This concept which had first appeared in Europe as a response to the crisis of the welfare State has now gained considerable currency over the last five years in both official and development discourses in Nepal. The issue gained considerable leverage when the Nepal Government recognized inclusion as a policy issue as one of the four pillars of 2003 Poverty Reduction Strategy Paper (PRSP), which is also Nepal's Tenth Plan. The debates surrounding inclusion/exclusion have ascended to conspicuous importance in the present political transition in Nepal with several groups such as Dalit, women, ethnic communities, donor communities, Madhesi communities and region voicing their demands for an inclusive state by virtue of which, the issue has now come to be a part of the popular public discourse. However, what has to be borne in mind is that the concept lacks universality in the way it has been defined and employed. While some claim that social exclusion is more illuminating and holds the promise of understanding disadvantaged groups better, others argue that this concept is so evocative, ambiguous, multidimensional and elastic that it can be defined in many different ways and owing to its ambiguity in definition it may mean all things to all people. Howsoever, the term has been used, defined, conceptualized, the article here makes an effort to review accessible literature on the topic. DOI = 10.3126/dsaj.v2i0.1362 Dhaulagiri Journal of Sociology and Anthropology Vol.2 pp.161-180